Implementing quality and re-engineereing programmes : managing the people issues - Mc Bain, Richard (1999)
Considers recent research which provides and insight into a number of key issues in implementing programmes such as Total Quality Management and Business Process Re-engineering, including: the importance of context; the impact of corportate and national cultures; employee commitment; issues of justice; the impact of the external environment; and, managing the change process.